Preparation method of metal surface hard welding layer

By combining modified tungsten carbide-cobalt carbide with nickel-based alloy powder and cermet particles, a composite hard solder layer is formed, which solves the problems of wear weight loss and thermal fatigue of the existing hard solder layer in harsh environments, and achieves higher hardness and wear resistance.

CN119681482AActive Publication Date: 2025-03-25NANJING TIANBAOCHANG METALLURGICAL MASCH PARTS CO LTD

Patent Information

Application Number
CN202510203333.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-24
Publication Date
2025-03-25
Estimated Expiration
2045-02-24

AI Technical Summary

Technical Problem

The existing hard solder layer is prone to wear and lose weight in harsh environments, and cannot effectively withstand thermal fatigue testing, and is prone to cracks and other problems.

Method used

Modified tungsten carbide-cobalt is used to prepare cemented carbide, and combined with nickel-based alloy powder and metal cermet particles, a composite hard solder layer is formed on the surface of the steel base material, and the solder layer is fixed through bump welding and oxyacetylene flame spray welding technology.

Benefits of technology

Effectively increase the hardness of the solder layer, reduce wear, can withstand thermal fatigue testing, and obtain good wear resistance and high temperature resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides a preparation method of a metal surface hard welding layer, and belongs to the technical field of metal material surface treatment. The modified tungsten-cobalt carbide is used for preparing the hard alloy, the nickel-based alloy powder and the metal ceramic particles are used together, the composite hard welding layer is obtained on the surface of the steel part base material, the hardness of the welding layer is effectively improved, meanwhile, the abrasion condition of the welding layer in use is reduced, and a thermal fatigue test can be effectively borne; and good wear resistance and high temperature resistance are obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal material surface treatment, and in particular relates to a method for preparing a hard welding layer on a metal surface. Background Art

[0002] Metal surface modification technology refers to a type of heat treatment technology that uses chemical and physical methods to change the chemical composition and organizational structure of the surface of materials or workpieces in order to improve the performance of machine parts or materials, including surface deformation modification, surface heat treatment, surface chemical heat treatment, surface coating and thin film coating; in the fields of steel metallurgy, petrochemicals, mining machinery, etc., surface modification can improve the performance of materials, improve product quality and reduce enterprise costs; in addition, surface modification can also increase the service life and reliability of parts and save materials and energy.

[0003] The Chinese patent (publication number CN113458553B) provides a wear-resistant high-entropy alloy surfacing layer and preparation method. The wear-resistant high-entropy alloy surfacing layer prepared by this method improves the disadvantage of small volume of traditional high-entropy alloy preparation to a certain extent. The wear-resistant surfacing layer can be prepared in large quantities by welding on the surface of the tool to meet the application of cutting tool materials. The hard surface materials of the existing metal surface strengthening technology have certain wear resistance and corrosion resistance functions, which can meet the general wear-resistant working conditions. However, for more severe working conditions, such as high temperature, high erosion, strong wear, etc., a single hard surface material and preparation method are difficult to meet the use requirements of wear-resistant parts; the preparation of a hard welding layer by a single material for metal surface modification has the problem that the welding layer is not hard enough, it is easy to wear and lose weight in harsh environments, and it is easy to crack when it cannot withstand thermal fatigue testing.

[0004] Therefore, how to obtain a composite hard welding layer on the metal surface by compounding multiple materials, effectively increasing the hardness of the welding layer, while reducing the wear during its use, and being able to effectively withstand thermal fatigue tests and obtain better wear resistance and high temperature resistance has become a direction that needs to be focused on. Summary of the invention

[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a method for preparing a hard welding layer on a metal surface, aiming to solve the problems of the existing hard welding layer, such as insufficient hardness of the welding layer, easy weight loss due to wear in harsh environments, and easy cracking when unable to withstand thermal fatigue tests.

[0006] The present invention uses modified tungsten carbide-cobalt to prepare cemented carbide, and uses it together with nickel-based alloy powder and metal ceramic particles to obtain a composite hard welding layer on the surface of a steel substrate, which effectively increases the hardness of the welding layer while reducing its wear during use, and can effectively withstand thermal fatigue tests to obtain better wear resistance and high temperature resistance.

[0007] The technical solution of the present invention is as follows: The present invention provides a method for preparing a hard solder layer on a metal surface, comprising the following steps: Step S1: sequentially subjecting the steel substrate to surface sandblasting, surface degreasing, ultrasonic cleaning and dehydration and drying to obtain a roughened steel substrate; Step S2: loading tungsten carbide-cobalt powder into a mold with convex points, and performing spark plasma sintering to obtain a tungsten carbide-cobalt cemented carbide sheet with convex points; Step S3: placing the tungsten carbide-cobalt cemented carbide sheet with convex points in step S2 on the surface of the roughened steel substrate in step S1, fixing the tungsten carbide-cobalt cemented carbide sheet on the surface of the steel substrate by convex point welding, and obtaining a steel substrate welded with the cemented carbide sheet; Step S4: Fill the solder onto the surface of the steel substrate welded with the cemented carbide sheet in step S3 by oxyacetylene flame spray welding, and obtain a metal surface hard welding layer after grinding.

[0008] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.

[0009] Preferably, the blasting pressure of the surface sandblasting treatment in step S1 is 0.35-0.55 MPa, and the surface roughness Ra value of the steel substrate after sandblasting is 6-8 μm; the ultrasonic frequency of the ultrasonic cleaning treatment is 20-40 KHz.

[0010] As a preferred technical solution of the present invention, the tungsten carbide-cobalt powder in step S2 is modified tungsten carbide-cobalt powder; The preparation method of the modified tungsten carbide-cobalt powder comprises: In parts by weight, 80-90 parts of tungsten powder, 8-10 parts of cobalt powder, 6-8 parts of boron powder, 4-6 parts of carbon black and 3-5 parts of glucose are mixed and ball-milled, vacuum dried and sieved to obtain a mixed powder; 4-6 parts of paraffin are added to 350-400 parts of anhydrous ethanol, stirred for 1-2 hours, and then the mixed powder is added, and the water bath heating and stirring are continued until the anhydrous ethanol evaporates to form a viscous slurry, and the viscous slurry is vacuum dried and sieved to obtain a tungsten carbide-cobalt mixed powder; 5-8 parts of ammonium citrate are added to 100-120 parts of deionized water to form an ammonium citrate solution, and the ammonium citrate solution is hydrothermally reacted at a temperature of 180-185° C. for 20-24 hours to obtain an N-doped carbon quantum dot stock solution; 10-20 parts of the tungsten carbide-cobalt mixed powder are added to the N-doped carbon quantum dot stock solution, reacted for 30 hours under light-proof conditions, and freeze-dried after the reaction is completed to obtain a modified tungsten carbide-cobalt powder.

[0011] The modified tungsten carbide-cobalt cemented carbide contains N-doped carbon quantum dots. The surface of the N-doped carbon quantum dots contains rich nitrogen-containing and oxygen-containing functional groups. These functional groups can be adsorbed on the positively charged sites on the friction surface, where they act as "bearing balls" and react with the worn surface to form a lubricating film, thereby effectively preventing the wear of the weld layer; in addition, the boron element in the alloy can be concentrated at the grain boundary, reducing the sliding and cracking tendency of the grain boundary, enhancing the stability of the grain boundary, and slowing down the atomic diffusion rate at the grain boundary, reducing the migration speed of the grain boundary at high temperature, and improving the thermal stability of the grain boundary, thereby reducing the thermal fatigue crack propagation length.

[0012] Preferably, the sintering process in step S2 includes: The sintering pressure is 40~100MPa, the heating rate is 20~30℃ / min, the temperature is raised from room temperature to 850~880℃ and kept for 15~25min, then raised to 1040~1060℃ and kept for 15~25min, and finally raised to 1210~1240℃ and kept for 10~15min. After the holding period, the heating is stopped and the furnace is cooled to room temperature to obtain tungsten carbide-cobalt cemented carbide with convex points.

[0013] Preferably, the number of bumps in the bump welding in step S3 is 4 to 6, the height of the bumps is 0.3 to 0.5 mm, and the instantaneous current passing through the bump welding is 10000 to 15000 A.

[0014] As a preferred technical solution of the present invention, the solder in step S4 is nickel-based alloy powder and metal ceramic particles; the mass ratio of the nickel-based alloy powder to the metal ceramic particles is (2-3):1.

[0015] As a preferred technical solution of the present invention, the method for preparing the nickel-based alloy powder comprises: In parts by weight, 3 to 5 parts of nickel powder, 3 to 5 parts of chromium powder and 10 to 12 parts of graphene oxide are added to 100 to 120 parts of deionized water, and the mixture is ball-milled to obtain a mixed solution; the mixed solution is freeze-dried to obtain a nickel-based alloy powder.

[0016] Nickel-based alloy powder is compounded with nickel and chromium through graphene oxide. The nickel element has excellent corrosion resistance and oxidation resistance, which can improve the corrosion and wear resistance of the weld layer; while the chromium element can be dispersed between dendrites to produce dispersion strengthening, forming fine second phase particles and dispersed in the matrix, hindering dislocation movement, thereby increasing the overall hardness of the weld layer.

[0017] As a preferred technical solution of the present invention, the method for preparing the metal ceramic particles comprises: In parts by weight, 10 to 12 parts of iron powder, 10 to 12 parts of molybdenum powder, 6 to 8 parts of manganese powder, 4 to 6 parts of tungsten powder and 4 to 6 parts of cobalt powder are weighed and added into a ball mill, ball-milled under a nitrogen atmosphere, and mixed evenly to obtain a high-entropy alloy powder; 10 to 15 parts of nano-alumina and 5 to 10 parts of graphene oxide are added to 80 to 90 parts of anhydrous ethanol, ultrasonically dispersed for 20 to 30 minutes, and then the high-entropy alloy powder is added and stirred for 2 to 4 hours. After stirring, vacuum drying is performed for 10 to 12 hours, and metal ceramic particles are sieved.

[0018] There is a big difference between the size of nano-alumina in the metal ceramic particles and the cemented carbide phase, which will form an intergranular or intragranular structure. When the nano-alumina is in the crack propagation path, it can prevent the crack from propagating through the "pinning effect", thereby reducing the thermal fatigue crack propagation length; at the same time, high-entropy alloys contain iron, molybdenum, manganese, tungsten, cobalt and other elements, which can form solid solutions in the cemented carbide matrix, resulting in lattice distortion, increasing the resistance to dislocation movement, and thus improving the hardness of the weld layer.

[0019] Preferably, the oxyacetylene flame spray welding in step S4 adopts a neutral flame, the acetylene gas pressure is 0.08-0.14 MPa, and the oxygen pressure is 0.4-0.6 MPa.

[0020] Preferably, the nozzle diameter of the spray welding gun in step S4 is 2-4 mm; the solder powder feeding amount is 50-80 g / min, and the implementation distance of the spray welding is 250-300 mm.

[0021] Compared with the prior art, the present invention has the following beneficial effects: (1) The chromium element contained in the nickel-based alloy powder of the present invention can be dispersed between dendrites to produce dispersion strengthening, forming fine second phase particles and dispersed in the matrix, hindering dislocation movement; and the metal ceramic particles, on the one hand, penetrate into the modified tungsten carbide-cobalt cemented carbide through the metal elements of the high entropy alloy, and on the other hand, are connected to the nickel-based alloy powder through graphene oxide, which effectively improves the density of the weld layer during the processing process, and increases the hardness of the weld layer through the joint action of the nickel-based alloy powder and the metal ceramic particles.

[0022] (2) In the cemented carbide of the present invention, the nitrogen- and oxygen-containing functional groups rich in the surface of the N-doped carbon quantum dots are adsorbed on the positively charged sites on the friction surface, reacting with the worn surface to form a lubricating film, thereby effectively preventing the wear of the weld layer; and the nickel element in the nickel-based alloy powder has excellent corrosion resistance and oxidation resistance, which can improve the corrosion and wear resistance of the weld layer.

[0023] (3) The cemented carbide of the present invention contains boron element, which can be concentrated at the grain boundary, reduce the sliding and cracking tendency of the grain boundary, enhance the stability of the grain boundary, slow down the atomic diffusion rate at the grain boundary, reduce the migration speed of the grain boundary at high temperature, and improve the thermal stability of the grain boundary; at the same time, there is a large difference between the size of the nano-alumina in the metal ceramic particles and the cemented carbide phase. When the nano-alumina is in the crack propagation path, it can prevent the crack from propagating through the "pinning effect", and through the synergistic effect of the cemented carbide and the metal ceramic particles, the thermal fatigue crack propagation length is reduced.

[0024] (4) The bottom convex point of the cemented carbide sheet of the present invention has a small contact area with the metal substrate during welding, and a large current passes through it instantly during welding, causing the convex point and the metal substrate surface in contact to melt slightly, and the two penetrate each other, solidify after instantaneous cooling, so that the alloy sheet is firmly bonded to the surface of the substrate metal; the nickel-based alloy powder in the solder has good cladding performance, can firmly grasp the metal ceramic particles, and together with the cemented carbide sheet form a composite welding layer that is resistant to high temperature, wear and corrosion. DETAILED DESCRIPTION

[0025] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0026] The sources of some components in the embodiments and comparative examples are as follows: Tungsten powder, catalog number PA86875, was purchased from Shanghai Chuangsai Technology Co., Ltd.; Cobalt powder, product number PA20195, was purchased from Shanghai Chuangsai Technology Co., Ltd.; Boron powder, product number PA07655, was purchased from Shanghai Chuangsai Technology Co., Ltd.; Carbon black, product number SUPER P Li, was purchased from Guangdong Lvwei New Materials Technology Co., Ltd.; Glucose, CAS No. 50-99-7, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; Paraffin wax, CAS No. 8002-74-2, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Anhydrous ethanol, CAS No. 64-17-5, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Ammonium citrate, CAS No. 7632-50-0, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; Nickel powder, item number W5, purchased from Huizhou Tenghui Technology Co., Ltd.; Chromium powder, product number PA20257, was purchased from Shanghai Chuangsai Technology Co., Ltd.; Graphene oxide, product number CNT901, was purchased from Zhongke Leiming (Beijing) Technology Co., Ltd.; Iron powder, item number PA28223, was purchased from Shanghai Chuangsai Technology Co., Ltd.; Molybdenum powder, product number PA58522, was purchased from Shanghai Chuangsai Technology Co., Ltd.; Manganese powder, product number M105838, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; Nano-alumina, CAS No. 1302-74-5, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Commercially available tungsten carbide-cobalt powder, item number GWC-12, purchased from ATI Engineered Products, USA; Commercially available alumina ceramic powder, item number AL-160SG-3, was purchased from Guangzhou Qihua Chemical Co., Ltd.

[0027] Preparation of modified tungsten carbide-cobalt powder: In parts by weight, 90 parts of tungsten powder, 10 parts of cobalt powder, 8 parts of boron powder, 6 parts of carbon black and 5 parts of glucose are mixed and ball-milled, and vacuum dried and sieved to obtain a mixed powder; 6 parts of paraffin are added to 400 parts of anhydrous ethanol, stirred for 2 hours, and then the mixed powder is added, and the water bath heating and stirring are continued until the anhydrous ethanol evaporates to form a viscous slurry, and the viscous slurry is vacuum dried and sieved to obtain a tungsten carbide-cobalt mixed powder; 8 parts of ammonium citrate are added to 100 parts of deionized water to form an ammonium citrate solution, and the ammonium citrate solution is hydrothermally reacted at a temperature of 180°C for 24 hours to obtain an N-doped carbon quantum dot stock solution; 20 parts of the tungsten carbide-cobalt mixed powder are added to the N-doped carbon quantum dot stock solution, and the reaction is carried out in a dark environment for 30 hours. After the reaction is completed, the modified tungsten carbide-cobalt powder is obtained by freeze drying.

[0028] Preparation of nickel-based alloy powder: In parts by weight, 5 parts of nickel powder, 5 parts of chromium powder and 12 parts of graphene oxide are added to 100 parts of deionized water, and ball-milled to obtain a mixed solution; the mixed solution is freeze-dried to obtain a nickel-based alloy powder.

[0029] Preparation of metal ceramic particles: weigh 12 parts of iron powder, 12 parts of molybdenum powder, 8 parts of manganese powder, 6 parts of tungsten powder and 6 parts of cobalt powder by weight, add them into a ball mill, ball mill them under a nitrogen atmosphere, and mix them evenly to obtain high entropy alloy powder; add 15 parts of nano-alumina and 10 parts of graphene oxide to 90 parts of anhydrous ethanol, ultrasonically disperse them for 30 minutes, then add the high entropy alloy powder and stir for 4 hours. After stirring, vacuum dry it for 12 hours and sieve it to obtain metal ceramic particles.

[0030] Example 1 This embodiment provides a method for preparing a hard solder layer on a metal surface, comprising the following steps: Step S1: performing surface sandblasting, surface degreasing, ultrasonic cleaning and dehydration drying on the steel substrate in sequence to obtain a roughened steel substrate; the sandblasting pressure of the surface sandblasting is 0.55 MPa, and the surface roughness Ra value of the steel substrate after sandblasting is 8 μm; the ultrasonic frequency of the ultrasonic cleaning is 40 KHz; Step S2: loading the modified tungsten carbide-cobalt powder into a mold with convex points, and performing a discharge plasma sintering treatment to obtain a tungsten carbide-cobalt cemented carbide sheet with convex points; the sintering pressure of the sintering treatment is 100 MPa, the heating rate is 30°C / min, the temperature is raised from room temperature to 880°C and kept for 15 minutes, then raised to 1060°C and kept for 15 minutes, and finally raised to 1240°C and kept for 10 minutes. After the end of the heat preservation, the heating is stopped and the furnace is cooled to room temperature; Step S3: placing the tungsten carbide-cobalt cemented carbide sheet with bumps described in step S2 on the surface of the roughened steel substrate described in step S1, and fixing the tungsten carbide-cobalt cemented carbide sheet on the surface of the steel substrate by bump welding to obtain a steel substrate welded with the cemented carbide sheet; the number of bumps in the bump welding is 6, the height of the bump is 0.5 mm, and the instantaneous current passing through the bump welding is 15000 A; Step S4: Fill the solder (the mass ratio of nickel-based alloy powder and metal ceramic particles is 3:1) onto the surface of the steel substrate welded with the cemented carbide sheet in step S3 by oxyacetylene flame spray welding, wherein the oxyacetylene flame spray welding adopts a neutral flame, the acetylene gas pressure is 0.14 MPa, and the oxygen pressure is 0.6 MPa; the nozzle diameter of the spray welding gun is 4 mm; the solder powder feeding amount is 80 g / min, and the implementation distance of the spray welding is 300 mm; and finally, a hard welding layer on the metal surface is obtained after grinding.

[0031] Example 2 This embodiment provides a method for preparing a hard solder layer on a metal surface, comprising the following steps: Step S1: performing surface sandblasting, surface degreasing, ultrasonic cleaning and dehydration drying on the steel substrate in sequence to obtain a roughened steel substrate; the sandblasting pressure of the surface sandblasting is 0.35 MPa, and the surface roughness Ra value of the steel substrate after sandblasting is 6 μm; the ultrasonic frequency of the ultrasonic cleaning is 20 KHz; Step S2: loading the modified tungsten carbide-cobalt powder into a mold with convex points, and performing a discharge plasma sintering treatment to obtain a tungsten carbide-cobalt cemented carbide sheet with convex points; the sintering pressure of the sintering treatment is 40 MPa, the heating rate is 30°C / min, the temperature is raised from room temperature to 850°C and kept for 25 minutes, then raised to 1040°C and kept for 25 minutes, and finally raised to 1210°C and kept for 15 minutes. After the end of the heat preservation, the heating is stopped and the furnace is cooled to room temperature; Step S3: placing the tungsten carbide-cobalt cemented carbide sheet with bumps described in step S2 on the surface of the roughened steel substrate described in step S1, and fixing the tungsten carbide-cobalt cemented carbide sheet on the surface of the steel substrate by bump welding to obtain a steel substrate welded with the cemented carbide sheet; the number of bumps in the bump welding is 4, the height of the bump is 0.3 mm, and the instantaneous current passing through the bump welding is 10000 A; Step S4: Fill the solder (nickel-based alloy powder and metal ceramic particles in a mass ratio of 2:1) onto the surface of the steel substrate welded with the cemented carbide sheet in step S3 by oxyacetylene flame spray welding, wherein the oxyacetylene flame spray welding adopts a neutral flame, the acetylene gas pressure is 0.08 MPa, and the oxygen pressure is 0.4 MPa; the nozzle diameter of the spray welding gun is 2 mm; the solder powder feeding rate is 50 g / min, and the spray welding implementation distance is 250 mm; and finally, a hard welding layer on the metal surface is obtained after grinding.

[0032] Example 3 This embodiment provides a method for preparing a hard solder layer on a metal surface, comprising the following steps: Step S1: performing surface sandblasting, surface degreasing, ultrasonic cleaning and dehydration drying on the steel substrate in sequence to obtain a roughened steel substrate; the sandblasting pressure of the surface sandblasting is 0.45 MPa, and the surface roughness Ra value of the steel substrate after sandblasting is 7 μm; the ultrasonic frequency of the ultrasonic cleaning is 30 KHz; Step S2: loading the modified tungsten carbide-cobalt powder into a mold with convex points, and performing a discharge plasma sintering treatment to obtain a tungsten carbide-cobalt cemented carbide sheet with convex points; the sintering pressure of the sintering treatment is 80 MPa, the heating rate is 25°C / min, the temperature is raised from room temperature to 860°C and kept for 20 minutes, then raised to 1050°C and kept for 20 minutes, and finally raised to 1220°C and kept for 12 minutes. After the end of the heat preservation, the heating is stopped and the furnace is cooled to room temperature; Step S3: placing the tungsten carbide-cobalt cemented carbide sheet with bumps described in step S2 on the surface of the roughened steel substrate described in step S1, and fixing the tungsten carbide-cobalt cemented carbide sheet on the surface of the steel substrate by bump welding to obtain a steel substrate welded with the cemented carbide sheet; the number of bumps in the bump welding is 5, the height of the bump is 0.4 mm, and the instantaneous current passing through the bump welding is 12000 A; Step S4: Fill the solder (nickel-based alloy powder and metal ceramic particles in a mass ratio of 3:1) onto the surface of the steel substrate welded with the cemented carbide sheet in step S3 by oxyacetylene flame spray welding, wherein the oxyacetylene flame spray welding adopts a neutral flame, the acetylene gas pressure is 0.12 MPa, and the oxygen pressure is 0.5 MPa; the nozzle diameter of the spray welding gun is 3 mm; the solder powder feeding rate is 60 g / min, and the spray welding implementation distance is 260 mm; and finally, a hard welding layer on the metal surface is obtained after grinding.

[0033] Comparative Example 1 This comparative example provides a method for preparing a hard welding layer on a metal surface. The difference from Example 1 is that commercially available tungsten carbide-cobalt powder is used instead of modified tungsten carbide-cobalt powder, commercially available nickel powder is used instead of nickel-based alloy powder, and commercially available alumina ceramic powder is used instead of metal ceramic particles. Other conditions are the same as those in Example 1.

[0034] Comparative Example 2 This comparative example provides a method for preparing a hard welding layer on a metal surface. The difference from Example 1 is that commercially available nickel powder is used instead of nickel-based alloy powder, and commercially available alumina ceramic powder is used instead of metal ceramic particles. Other conditions are the same as those in Example 1.

[0035] Comparative Example 3 This comparative example provides a method for preparing a hard welding layer on a metal surface. The difference from Example 1 is that commercially available tungsten carbide-cobalt powder is used instead of modified tungsten carbide-cobalt powder, and commercially available alumina ceramic powder is used instead of metal ceramic particles. Other conditions are the same as those in Example 1.

[0036] Comparative Example 4 This comparative example provides a method for preparing a hard welding layer on a metal surface. The difference from Example 1 is that commercially available tungsten carbide-cobalt powder is used instead of modified tungsten carbide-cobalt powder, and commercially available nickel powder is used instead of nickel-based alloy powder. Other conditions are the same as those in Example 1.

[0037] Comparative Example 5 This comparative example provides a method for preparing a hard welding layer on a metal surface. The difference from Example 1 is that commercially available tungsten carbide-cobalt powder is used instead of modified tungsten carbide-cobalt powder, and other conditions are the same as those in Example 1.

[0038] Comparative Example 6 This comparative example provides a method for preparing a hard welding layer on a metal surface. The difference from Example 1 is that commercially available nickel powder is used instead of nickel-based alloy powder, and other conditions are the same as those in Example 1.

[0039] Comparative Example 7 This comparative example provides a method for preparing a hard welding layer on a metal surface. The difference from Example 1 is that commercially available alumina ceramic powder is used instead of metal ceramic particles, and other conditions are the same as those in Example 1.

[0040] The performance of the hard solder layer provided in the above embodiments and comparative examples was tested, and the testing method was as follows: Hardness test: A microhardness tester (model HV-1000, Shanghai Gaozhi Precision Instrument Co., Ltd.) was used to test the microhardness of the weld layer. The load required for the test was 0.2kgf, and the loading time was 10s. The test point was close to the surface of the weld layer (about 0.25mm from the surface) as the zero point, and the hardness value was tested at an interval of 0.5mm towards the heat-affected zone of the substrate.

[0041] Wear resistance test: Use an electric spark wire cutting machine to cut the weld layer into a sample with a size of 17mm×14mm×4mm, use water-resistant sandpaper for coarse and fine grinding, and then clean the sample with acetone; the test uses a dry rubber wheel abrasive wear tester (model MLG-130, Zhangjiakou Chengxin Testing Equipment Manufacturing Co., Ltd.), the rubber wheel diameter is 228mm, the hardness is 60HS, the speed is 120r / min, the abrasive is 50 mesh quartz sand, the test load is 45N, and the wear time is 30min; the mass of the sample is measured by an electronic balance before and after the test, and the wear resistance is characterized by the wear weight loss rate; the wear weight loss rate formula is as follows:

[0042] Where η is the weight loss rate due to wear, 𝑚0 is the mass of the sample before wear, and 𝑚1 is the mass of the sample after wear.

[0043] Thermal fatigue test: The weld layer was prepared into thermal fatigue specimens according to the requirements of YB / T 4326-2013 by using an electric spark wire cutting machine. The thermal fatigue test was carried out at a high temperature of 700°C, an accuracy of 5°C, and a holding time of 120s; the test was carried out by water cooling to room temperature of 20°C and a cooling time of 15s. The specimens after 800 thermal fatigue tests were ground and polished, and the thermal fatigue crack extension length of the specimens was measured.

[0044] The above performance test data is shown in Table 1.

[0045] Table 1 Performance test results

[0046] From the above content, it can be seen that the present invention prepares cemented carbide by using modified tungsten carbide-cobalt, and uses it together with nickel-based alloy powder and metal ceramic particles to obtain a composite hard welding layer on the surface of a steel substrate (Example 1 to Example 3), whose hardness is 847~851HV, the wear weight loss rate is 0.63~0.65%, and the thermal fatigue crack extension length is 0.92~0.96mm.

[0047] Compared with Example 1, the modified tungsten carbide-cobalt powder is replaced by commercially available tungsten carbide-cobalt powder, the nickel-based alloy powder is replaced by commercially available nickel powder, and the metal ceramic particles are replaced by commercially available alumina ceramic powder, the hardness is reduced, the wear weight loss rate is increased, and the thermal fatigue crack propagation length is increased (Comparative Example 1); Compared with Example 1, the nickel-based alloy powder is replaced by commercially available nickel powder, and the metal ceramic particles are replaced by commercially available alumina ceramic powder, the hardness is reduced, the wear weight loss rate is increased, and the thermal fatigue crack propagation length is increased (Comparative Example 2); Compared with Example 1, the modified tungsten carbide-cobalt powder is replaced by commercially available tungsten carbide-cobalt powder, and the metal ceramic particles are replaced by commercially available alumina ceramic powder, the hardness is reduced, the wear weight loss rate is increased, and the thermal fatigue crack propagation length is increased. Increase (Comparative Example 3); Compared with Example 1, commercially available tungsten carbide-cobalt powder is used to replace the modified tungsten carbide-cobalt powder, and commercially available nickel powder is used to replace the nickel-based alloy powder, the hardness decreases, the wear weight loss rate increases, and the thermal fatigue crack propagation length increases (Comparative Example 4); Compared with Example 1, commercially available tungsten carbide-cobalt powder is used to replace the modified tungsten carbide-cobalt powder, the hardness decreases, the wear weight loss rate increases, and the thermal fatigue crack propagation length increases (Comparative Example 5); Compared with Example 1, commercially available nickel powder is used to replace the nickel-based alloy powder, the hardness decreases, and the wear weight loss rate increases (Comparative Example 6); Compared with Example 1, commercially available alumina ceramic powder is used to replace metal ceramic particles, the hardness decreases, and the thermal fatigue crack propagation length increases (Comparative Example 7).

[0048] In summary, the present invention prepares cemented carbide by using modified tungsten carbide-cobalt, and uses it together with nickel-based alloy powder and metal ceramic particles to obtain a composite hard welding layer on the surface of a steel substrate, which effectively increases the hardness of the welding layer while reducing its wear during use, and can effectively withstand thermal fatigue tests, thereby obtaining better wear resistance and high temperature resistance.

[0049] The applicant declares that the present invention illustrates the detailed process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a hard solder layer on a metal surface, characterized in that: The following steps are involved: Step S1: sequentially subjecting the steel substrate to surface sandblasting, surface degreasing, ultrasonic cleaning and dehydration and drying to obtain a roughened steel substrate; Step S2: loading tungsten carbide-cobalt powder into a mold with convex points, and performing spark plasma sintering to obtain a tungsten carbide-cobalt cemented carbide sheet with convex points; Step S3: placing the tungsten carbide-cobalt cemented carbide sheet with convex points in step S2 on the surface of the roughened steel substrate in step S1, fixing the tungsten carbide-cobalt cemented carbide sheet on the surface of the steel substrate by convex point welding, and obtaining a steel substrate welded with the cemented carbide sheet; Step S4: filling the solder onto the surface of the steel substrate welded with the cemented carbide sheet in step S3 by oxyacetylene flame spray welding, and obtaining a hard welding layer on the metal surface after grinding; The tungsten carbide-cobalt powder in step S2 is a modified tungsten carbide-cobalt powder; The preparation method of the modified tungsten carbide-cobalt powder comprises: by weight, mixing 80-90 parts of tungsten powder, 8-10 parts of cobalt powder, 6-8 parts of boron powder, 4-6 parts of carbon black and 3-5 parts of glucose, ball milling, vacuum drying and sieving to obtain a mixed powder; adding 4-6 parts of paraffin wax to 350-400 parts of anhydrous ethanol, stirring for 1-2 hours, then adding the mixed powder, continuously heating and stirring in a water bath until the anhydrous ethanol evaporates to form a viscous slurry, vacuum drying and sieving the viscous slurry, and obtaining to a tungsten carbide-cobalt mixed powder; adding 5 to 8 parts of ammonium citrate to 100 to 120 parts of deionized water to form an ammonium citrate solution, and hydrothermally reacting the ammonium citrate solution at a temperature of 180 to 185° C. for 20 to 24 hours to obtain an N-doped carbon quantum dot stock solution; adding 10 to 20 parts of the tungsten carbide-cobalt mixed powder to the N-doped carbon quantum dot stock solution, reacting for 30 hours under light-proof conditions, and freeze-drying after the reaction to obtain a modified tungsten carbide-cobalt powder.

2. The method for preparing a metal surface hard solder layer according to claim 1, characterized in that: The blasting pressure of the surface sandblasting treatment in step S1 is 0.35-0.55 MPa, and the surface roughness Ra value of the steel substrate after sandblasting is 6-8 μm; the ultrasonic frequency of the ultrasonic cleaning treatment is 20-40 KHz.

3. The method for preparing a metal surface hard solder layer according to claim 1, characterized in that: The sintering process described in step S2 includes: sintering pressure of 40~100MPa, heating rate of 20~30℃ / min, heating from room temperature to 850~880℃ and keeping warm for 15~25min, then heating to 1040~1060℃ and keeping warm for 15~25min, and finally heating to 1210~1240℃ and keeping warm for 10~15min. After the insulation is completed, heating is stopped and cooled to room temperature with the furnace to obtain tungsten carbide-cobalt cemented carbide with protrusions.

4. The method for preparing a metal surface hard solder layer according to claim 1, characterized in that: The number of bumps in the bump welding in step S3 is 4 to 6, the height of the bumps is 0.3 to 0.5 mm, and the instantaneous current passing through the bump welding is 10000 to 15000 A.

5. The method for preparing a metal surface hard solder layer according to claim 1, characterized in that: The solder in step S4 is nickel-based alloy powder and metal ceramic particles; the mass ratio of the nickel-based alloy powder to the metal ceramic particles is (2-3):

1.

6. The method for preparing a metal surface hard solder layer according to claim 5, characterized in that: The preparation method of the nickel-based alloy powder comprises: adding 3 to 5 parts of nickel powder, 3 to 5 parts of chromium powder and 10 to 12 parts of graphene oxide to 100 to 120 parts of deionized water by weight, and mixing by ball milling to obtain a mixed solution; and freeze-drying the mixed solution to obtain the nickel-based alloy powder.

7. The method for preparing a metal surface hard solder layer according to claim 5, characterized in that: The preparation method of the metal ceramic particles comprises: weighing 10 to 12 parts of iron powder, 10 to 12 parts of molybdenum powder, 6 to 8 parts of manganese powder, 4 to 6 parts of tungsten powder and 4 to 6 parts of cobalt powder in parts by weight, adding them into a ball mill, ball milling them under a nitrogen atmosphere, and mixing them evenly to obtain a high entropy alloy powder; adding 10 to 15 parts of nano-alumina and 5 to 10 parts of graphene oxide into 80 to 90 parts of anhydrous ethanol, ultrasonically dispersing them for 20 to 30 minutes, then adding the high entropy alloy powder and stirring for 2 to 4 hours, vacuum drying them for 10 to 12 hours after the stirring is completed, and sieving them to obtain the metal ceramic particles.

8. The method for preparing a metal surface hard solder layer according to claim 1, characterized in that: The oxyacetylene flame spray welding in step S4 adopts a neutral flame, the acetylene gas pressure is 0.08-0.14 MPa, and the oxygen pressure is 0.4-0.6 MPa.

9. The method for preparing a metal surface hard solder layer according to claim 1, characterized in that: The nozzle diameter of the spray welding gun in step S4 is 2-4 mm; the solder powder feeding amount is 50-80 g / min, and the implementation distance of the spray welding is 250-300 mm.

Citation Information

Patent Citations

  • A wear-resistant high-entropy alloy weld overlay and its preparation method

    CN113458553B

  • Composite hard-surface material and manufacturing method thereof

    CN105382389A

  • Preparation method of tungsten carbide-cobalt cemented carbide

    CN108486398A

  • Preparation method of gradient hard alloy sand mill part

    CN113770363A

  • Recycled diamond broken material and graphene composite doping modified nickel-based alloy material and preparation method thereof

    CN115786772A

Cited By

  • Conical lining plate for mine crusher

    CN121288913A